Respiratorische Notfälle und Atemwegsmanagement im Kindesalter = Respiratory emergencies and airway management in children - Demirakça, Süha (Medizinische Klinik, Intensivmedizin und Notfallmedizin, 2015)
Respiratory emergencies in children are frequent and are caused by the specific airway anatomy and the susceptibility for infections.This article reviews the specific approach to pediatric airway management. According to the ABC guidelines of the European Resuscitation Council, the described algorithm should help to identify, classify, and treat such emergencies, giving those with less pediatric experience a tool for the management of respiratory illness in children. Focus is on the emergency care of the most common diseases in this age group.